Women, love and power in Enlightenment Scotland. Issue 2 (23rd February 2018) - Barclay, Katie; Carr, Rosalind
ABSTRACT: The significance of the Enlightenment for women's power in society and culture has been a topic of significant historiographical debate. This article looks at how women were located within the discourse of the Scottish Enlightenment and its implications for elite women's role within public and private life in eighteenth-century Scotland. It argues that women were located as helpmeets to men, a designation that authorised their access to education and to some areas of public debate, but that their authority rested on their ability to improve the position of men, rather than enabling them as autonomous agents. To make this argument it draws together case studies of women's role in the home and family, with their engagement in public life and as authors, demonstrating how similar values shaped their role in each sphere.